CHARACTERISTICS STRENGTH OF COCONUT FIBER REINFORCED CONCRETE - Usman, Rufai; Osigbemhe, Itofa-Oghena; Ochi, Marycynthia Kosarachukwu; Oladejo, Samuel Taiwo; Osigbemhe, Ikpaobo-Oghena (FUDMA JOURNAL OF SCIENCES, 2025)
Sustainability is widely embraced in modern construction, despite rising costs and environmental harm from industry advancements. This has spurred a balanced, eco-centric approach, incorporating natural fibers like coconut for concrete reinforcement. Abundant at test sites, coconut fiber is a viable, eco-friendly option that boosts strength, cuts carbon emissions, and offers income for producers by repurposing coir waste, easing landfill pressure. High water absorption is mitigated by oil-coating the fibers. This study assessed coconut fiber-reinforced concrete’s strength, sourced from Ivbiaro, Owan West, Edo State. Using M20 grade concrete (1:2:4) with a 0.5 water-cement ratio, fibers were added at 1%, 2%, 3%, 4%, and 5%. Seventy-two cubes (150 x 150 x 150 mm) were cast, with 18 per mix ratio. Fresh concrete was tested for slump and compaction, while hardened concrete underwent rebound hammer (RH), ultrasonic velocity (UVT), and compressive strength tests at 7, 14, 21, and 28 days under lab conditions. Results showed workability decreases as fiber content rises, while density increases. Compressive strength peaks at 1% fiber (22.44 N/mm²) from 0% (19.87 N/mm²), but declines beyond 1%. Thus, coconut fiber enhances concrete sustainability and strength optimally at 1%, supporting eco-friendly construction with economic and waste management benefits.